Molecularly imprinted polymers as effective capturing receptors in a pseudo-ELISA immunoassay for procalcitonin detection in veterinary species. Issue 1 (9th December 2022) - Battaglia, Federica; Bonelli, Francesca; Sgorbini, Micaela; Intorre, Luigi; Minunni, Maria; Scarano, Simona; Meucci, Valentina
Abstract : Pseudo-ELISA innovative assay based on the combined use of biomimetic receptors (MIP) and antibodies for procalcitonin detection. Abstract : In this study, a new sandwich-type immunoenzymatic assay, based on a molecularly imprinted polymer (MIP) as an artificial antibody (pseudo-ELISA), was developed for the determination of procalcitonin (PCT) in veterinary species. The quantification of PCT in human medicine represents the state of the art for the diagnosis of sepsis; instead the clinical studies on the relevance of PCT as a sepsis predictor in veterinary patients are few, likely due to the total absence of validated assays. MIPs have been widely used as antibody mimics for important applications, and MIP-based sandwich assays have emerged as promising analytical tools for the detection of disease biomarkers. Herein, a polynorepinephrine (PNE)-based imprinted film was directly synthesized on the well surface of a 96-well plate. Subsequently, based on a commercial ELISA kit, the PCT quantification was accomplished via a colorimetric sandwich assay by replacing the capture antibody of the kit with the PNE-based MIP. This method was performed to detect canine and equine PCT in buffer and in plasma samples. Under optimal conditions, the results obtained in plasma samples showed a limit of detection (LOD) of 5.87 ng mL −1 and a reproducibility (CVav% ) of 10.0% for canine samples, while a LOD = 4.46 ng mL −1 and CVav% = 7.61% were obtained for equine samples.